(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article analyzes the characteristics of export formation and the structural composition of textile product exports in Uzbekistan. The study employs systemic and logical analysis, comparison, grouping, and economic-statistical methods. The findings indicate that cotton yarn and finished textile products occupy a leading position in the export structure, confirming the growing share of high value-added products in the light industry. At the same time, the relatively low share of certain product groups highlights the need for further export diversification. The results substantiate that the formation of textile exports is closely linked to the depth of the production chain, the level of technological development, and institutional support, and they can be used in making scientific and practical decisions aimed at export development.